Influences of Drying and Wetting Cycles and Compaction Degree on Strength of Yudong Silt for Subgrade and Its Prediction. (22nd July 2018) - Zhang, Junran; Jiang, Tong; Wang, Xingcui; Liu, Chong; Huang, Zhiquan
Abstract : In order to investigate the influences of drying and wetting cycles, initial degree of compaction, and water content on shear strength of the Yudong subgrade silt, a series of direct shear tests were performed at saturated and unsaturated states. The test results show that effects of the drying and wetting cycles, water content, and compaction degree on cohesion are more evident than those on the internal friction angle. According to the test data, a formula for the cohesion was proposed, which accounts for the drying and wetting cycles, water content, and degree of compaction. Because Bishop's strength formula for unsaturated soils could not be applied to Yudong silt, a formula is given based on Fredlund's formula for predicting the shear strength of unsaturated Yudong silt from the soil-water characteristic curve.